2023
DOI: 10.3390/nu15143284
|View full text |Cite
|
Sign up to set email alerts
|

Human Breast Milk microRNAs, Potential Players in the Regulation of Nervous System

Luis Freiría-Martínez,
Marta Iglesias-Martínez-Almeida,
Cynthia Rodríguez-Jamardo
et al.

Abstract: Human milk is the biological fluid with the highest exosome amount and is rich in microRNAs (miRNAs). These are key regulators of gene expression networks in both normal physiologic and disease contexts, miRNAs can influence many biological processes and have also shown promise as biomarkers for disease. One of the key aspects in the regeneration of the nervous system is that there are practically no molecules that can be used as potential drugs. In the first weeks of lactation, we know that human breast milk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 108 publications
0
6
0
Order By: Relevance
“…A recent study by our group in similar samples has identified 132 different miRNAs involved in the genetic regulation of dopaminergic/glutamatergic synapses and neurotransmitter secretion and related to the biological process that regulates neuronal projection morphogenesis and synaptic vesicle transport. 35 In this study, we analysed the proteins from exosomes obtained from different groups of breast milks.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study by our group in similar samples has identified 132 different miRNAs involved in the genetic regulation of dopaminergic/glutamatergic synapses and neurotransmitter secretion and related to the biological process that regulates neuronal projection morphogenesis and synaptic vesicle transport. 35 In this study, we analysed the proteins from exosomes obtained from different groups of breast milks.…”
Section: Resultsmentioning
confidence: 99%
“…Exosome extraction was done using an EX04 Exo-spinTM midi column (Cell Guidance Systems LTD, UK), optimized by our laboratory for human BM. 35 First, 1 mL of each milk sample was centrifuged at 16 000 × g for 30 min at 4 °C in order to remove cells and cellular debris. The entire supernatant including the layer of milk fat was transferred to a new 2 mL centrifuge and Exo-spinTM Buffer was added in a 1/1 ratio.…”
Section: Methodsmentioning
confidence: 99%
“…Bioinformatics analysis also offered indirect support for the functional hypothesis. For example, upregulated miRNAs in moderate/very preterm compared to term mature milk tended to be enriched in the neuro-related GO pathways ( 53 ). This result may indicate that BM miRNAs play a crucial role in infants' neurodevelopment ( 54 ).…”
Section: Bioavailability Of Bm-derived Mirnamentioning
confidence: 99%
“…The neuroprotective effects of these miRNAs are exerted by promoting neurogenesis, neurite remodeling and survival, and neuroplasticity [ 59 ]. Especially regarding neuroplasticity, many miRNAs are involved in synaptic plasticity [ 60 ], whereas several human milk exosomal miRNAs are implicated in the gene regulation of brain synapses and in synaptic vesicle trafficking [ 61 ]. It is worth mentioning that almost half of miRNAs with possible effects on synaptic development in mammals were found to be present in the top 288 miRNAs identified in human milk exosomes [ 62 ].…”
Section: Mirnasmentioning
confidence: 99%
“…Studies in animals also provided evidence that the exosomal content of human preterm breast milk has the potential to enable tissue healing in preterms with intestinal inflammation and protect against necrotizing enterocolitis [ 66 ]. Recent evidence has also shown significant differences between preterm and term human breast milk exosomes in several miRNAs associated with brain development and neurodevelopment including miR-3196, miR-1249-3p, miR-7847-3p, miR-1908-3p and miR-23b-3p, among others [ 61 ]. Further research in this area is needed.…”
Section: Mirnasmentioning
confidence: 99%